2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7592009
|View full text |Cite
|
Sign up to set email alerts
|

An innovative therapy for peri-implantitis based on radio frequency electric current: Numerical simulation results and clinical evidence

Abstract: Peri-implantitis is a severe inflammatory pathology that affects soit and hard tissues surrounding dental implants. Nowadays, only prevention is effective to contrast peri-implantitis, but, in recent years, there is the clinical evidence of the efficiency of a therapy based on the application of radio frequency electric current, reporting that 81% of the cases (66 implants, 46 patients) were successfully treated. The aim of this paper is to present the therapy mechanism, exploring the distribution of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Depending on the measured bioimpedance values and, thus, on the severity of the pathology, the therapeutic signal can be properly set to tune the treatment to the pathological conditions of the peri-implant tissues. The therapy consists of the application of a radio frequency (i.e., 312.5 kHz) alternating current burst, with a standard time duration of 120 ms and a peak power value of 6 W, passing through the tissues between the electrodes [32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the measured bioimpedance values and, thus, on the severity of the pathology, the therapeutic signal can be properly set to tune the treatment to the pathological conditions of the peri-implant tissues. The therapy consists of the application of a radio frequency (i.e., 312.5 kHz) alternating current burst, with a standard time duration of 120 ms and a peak power value of 6 W, passing through the tissues between the electrodes [32].…”
Section: Methodsmentioning
confidence: 99%
“…It is worthy to underline the fact that the EM signal acts just on the principal hallmarks of peri-implantitis: soft tissue inflammation, peri-implant bone loss, and bacterial growth. Hence, EM signal can be evaluated as a possible therapy for peri-implantitis disease; in the literature, there is a clinical study (started in 2002) exploring this possibility [32] and the same hypothesis was reported in Reference [19]. Therefore, it appears that the development of a novel therapeutic device based on EM radiation would be very promising for peri-implantitis treatment and would also have a great impact on the electromedical device market.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…To date, a number of studies have demonstrated the beneficial effects of direct electrical stimulation on alveolar bone regeneration without the use of electroactive biomaterials. [ 217 , 218 , 219 ] Kaynak et al. [ 217 ] showed the application of a capacitively coupled electrical field (CCEF) could enhance alveolar bone defect repair in a beagle dog model.…”
Section: Electroactive Scaffolds Can Facilitate Bone Regeneration Und...mentioning
confidence: 99%
“…Cosoli et al. [ 219 ] reported the application of a radio frequency current could mitigate inflammation (peri‐implantitis) around dental implants. Lastly, Kim et al.…”
Section: Electroactive Scaffolds Can Facilitate Bone Regeneration Und...mentioning
confidence: 99%